2020
DOI: 10.1177/1559325820946914
|View full text |Cite
|
Sign up to set email alerts
|

Phyllathin From Phyllanthus Amarus Ameliorates Epileptic Convulsion and Kindling Associated Post-Ictal Depression in Mice via Inhibition of NF-κB/TLR-4 Pathway

Abstract: Background: Epilepsy is a chronic, complex, unprovoked, and recurrent disorder of the nervous system that affected several people worldwide. Phyllanthus amarus (PA) has been documented to have neuroprotective potential. Aim: To evaluate the potential of standardized extract of PA and its possible mechanism of action against the Pentylenetetrazol (PTZ)-induced convulsion and kindling associated post-ictal depression in experimental mice. Materials and Methods: Phyllathin was isolated from methanolic extract of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(110 reference statements)
1
8
0
Order By: Relevance
“…Furthermore, TLR-4 being the major receptor for HMGB1 is a molecule of interest for assessing the pharmacological activity of potential ASDs ( 74 ). In this study, we observed increased levels of HMGB1 and TLR-4 in the vehicle + PTZ group, suggesting its role in epileptogenesis, which is in line with the previous studies where PTZ kindling resulted in increased mRNA expression of HMGB1 and TLR-4 in brain tissues of mice and zebrafish ( 75 , 76 ). Furthermore, the administration of fisetin suppressed the levels of HMGB1 and TLR-4 in the hippocampus and cortex of the kindled mice in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, TLR-4 being the major receptor for HMGB1 is a molecule of interest for assessing the pharmacological activity of potential ASDs ( 74 ). In this study, we observed increased levels of HMGB1 and TLR-4 in the vehicle + PTZ group, suggesting its role in epileptogenesis, which is in line with the previous studies where PTZ kindling resulted in increased mRNA expression of HMGB1 and TLR-4 in brain tissues of mice and zebrafish ( 75 , 76 ). Furthermore, the administration of fisetin suppressed the levels of HMGB1 and TLR-4 in the hippocampus and cortex of the kindled mice in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 92%
“…Scientists are trying to reduce neurodegeneration by using antioxidant compounds ( Lee et al, 2020 ). The present study depicted that O. limbata extract exerts its protective effect against elevated nitrosative stress ( Tao et al, 2020 ). The presence of the functional groups of bioactive compounds was confirmed through FTIR analysis.…”
Section: Discussionmentioning
confidence: 59%
“…Plants’ important role in brain cell protection in response to various types of traumas inflicted to brain is very fascinating. Studies have been reported where formulations with multiple phytoconstituents have proven to be therapeutically active in nervous system diseases ( Tao et al, 2020 ). O. persica has been reported for anticonvulsant activity ( Ansari et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous reports, the current study identified marked decreases in the levels of 5-HT and its metabolite (5-HIAA), DA, and NE and reduced AChE activity in PTZ-injected rats, which was accompanied by apparent increases in the DOPAC and HVA levels. Deficiencies in the levels of biogenic amines have been demonstrated to trigger seizure susceptibility and the development of behavioral deficits and neuropathological deficits in clinical and experimental studies [44][45][46]. Earlier reports showed a disturbance in the synthesis, release, and reuptake of monoamines following the initiation of epileptic seizures [47].…”
Section: Discussionmentioning
confidence: 99%